Superparamagnetic behaviour and deviation from Bloch T3/2 law of La0.7Ca0.3MnO3 nanoparticles. (8th April 2013) - Manh, Do Hung; Thanh, Tran Dang; Chien, Nguyen Van; Lam, Vu Dinh; Hong, Le Van; Phuc, Nguyen Xuan; Phong, Pham Thanh
In this study, we investigated superparamagnetism behaviour and saturation magnetisation of single–phase, nanocrystalline, granular La0.7 Ca0.3 MnO3 (LCMO) samples synthesised by reactive milling method. The superparamagnetic behaviour of as–milled samples with various milling times was studied in the temperature range from 200 K to 300 K. The saturation magnetisation of the samples increased from 14.7 to 36.8 emu/g with higher values corresponding to shorter milling time. The observed un–overlapping of the scaled M(Hext, T)/MS versus Hext /T plots and the Curie–Weiss like behaviour of the dc–susceptibility at high temperatures provide evidence that the nanoparticles are interacting superparamagnetic ensembles. The magnetisation curves of interacting nanoparticles were well described by the argument–corrected Langevin function. The saturation magnetisation versus temperature showed a T ε dependence with ε deviated from 3/2 (value for the Bloch law), which increased with decreasing of the milling time.